2006
DOI: 10.1080/09638280500386569
|View full text |Cite
|
Sign up to set email alerts
|

The use of rhythmic auditory cues to influence gait in patients with Parkinson's disease, the differential effect for freezers and non-freezers, an explorative study

Abstract: This study points to fact that physiotherapists might need to carefully adjust the cueing frequency to the needs of patients with and without freezing. On the basis of the present results we recommend to lower the frequency setting for freezers, whereas for non-freezers an increase of up to +10% may have potential therapeutic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
184
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 26 publications
26
184
1
2
Order By: Relevance
“…As step frequency was constrained to preferred rate it may be that subjects had difficulty matching the frequency of the cue. Performance during walking with the auditory cue agrees with previous work showing only small effects of the cue on step length and walking speed during a single task (Howe et al 2003;Willems et al 2006).…”
Section: Discussionsupporting
confidence: 80%
“…As step frequency was constrained to preferred rate it may be that subjects had difficulty matching the frequency of the cue. Performance during walking with the auditory cue agrees with previous work showing only small effects of the cue on step length and walking speed during a single task (Howe et al 2003;Willems et al 2006).…”
Section: Discussionsupporting
confidence: 80%
“…124,125 The effects of RAS may also carry over to none-RAS walking suggesting long-term retention effects. For example, after administration of RAS to PD patients for 3 weeks, an increase in gait speed and stride length has been observed, even when walking without stimulation.…”
Section: Effects Of Rhythmic Auditory Stimulationmentioning
confidence: 99%
“…e instruction given to the subjects was to synchronize each footstep in time to the metronome. e frequency of auditory cues was administered at 10% above the baseline stride 11 . Before the data collection, some practice trials were provided Procedures for the subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, therapy with auditory cues is also used as a sensory reinforcement for improving gait kinematic parameters of people with PD [11][12] . Recently, Rochester et al found that auditory cues have a positive role in gait kinematic parameters, which are resistant to dopaminergic treatment people with PD 13 .…”
Section: Introductionmentioning
confidence: 99%